Fabrication and characterisation of selected microwave absorbing ferrite-polymer composites - Mohd Idris, Fadzidah (2012)
Although absorbing materials are a useful part of modern-day defence systems, very little published knowledge exists on the fabrication of such materials especially microwave absorbing materials. The present research attempts to fabricate absorbing material compositions suitable for microwave absorption from 8 to 18 GHz. Various compositions of composite ferrites were prepared using mechanical alloying and sintering. The starting metal oxide raw materials were weighed according to the targeted proportion and milled for 10 hours using a SPEX8000D mill to get nanosized particles. The resulting mixture was poured into a PVA solution as a binder and stirred while drying it using an ultraviolet lamp until the powder contained ~1 wt% PVA. It was then pressed into pellet/toroid-shaped samples and sintered at temperature 900 °C for 10 hours. Then, a composite of ferrite powder with polymer paint as matrix was prepared. The composite paint produced was applied on the surface of a metal sheet of specified surface dimensions. Physical characteristics of the as-prepared filler samples were studied using X-ray diffraction (XRD), scanning transmission electron microscopy (STEM) and Field emission Scanning Electron Microscope (FESEM). The toroidal sample was further studied using an Agilent 4291B Impedance Analyzer with the frequency range from 1 MHz to 1 GHz in order to investigate the material‟s complex permeability components μ‟ and μ”. The absorption of the composite paint-coated metal sheet was characterized using an Agilent 85071E Network Analyzer in the frequency range from 8 GHz to 18 GHz. The XRD results show that at 900ºC the full phase of nickel zinc ferrite was formed. The average particle size for all the compositions is in nanometers(sub-micron sized). The resulting morphology was a homogeneous microstructure with small grain size and a uniform grain size distribution obtained via the mechanical alloying technique. From the complex permeability component μ‟ and μ” results, a significantly important result was established: that it was possible to extend the em energy absorption frequency range by reducing the grain size from micrometer to nanometer, using samples of the same chemical composition. For measurement at higher frequency (X-band and Ku-band), physical sample thickness influences the reflection loss and absorption of the ferrite-in-polymer-matrix composites with a metal back. Thicker samples result in higher microwave absorption. A sample with a thickness of 3.22 mm yields higher absorption compared to a sample with a thickness of 2.35 mm backed by an aluminium plate. Consequently, materials with different compositions give different levels of microwave absorption with the aluminium plate giving ~ 0 dB reflection losses. For other compositions, trends can be observed as the Ni2+ content is increased. As the Ni2+ content increases, the minimum reflection loss or maximum absorption is decreased. Therefore, Ni0.5Zn0.5Fe2O4 gives the highest absorption compared to that of other compositions. In addition, by comparing all the compositions involving combined nickel zinc ferrite (a mixture of nickel zinc ferrites with different NiZn ratios-NZF combine), Ni0.5Zn0.5Fe2O4 alone gives the most minimum reflection loss which corresponds to the highest absorption by the sample. The minimum reflection loss given by Ni0.5Zn0.5Fe2O4 at frequency 9.0 GHz and 12 GHz reaches – 6.72 dB and –11.2 dB respectively. Furthermore, the percentage amount of sintered Ni0.5Zn0.5Fe2O4 being added into the paint are 5 wt% and 20 wt% with different thicknesses. A higher ferrite content in the matrix resulting in higher absorption. The composite paints are expected to be very useful in military applications such as radar cross section reduction and prevention of electromagnetic interference.